Food security policy in South Africa, facing sectorial and territotial stakes : the complexity of public policies in a regionalized environment illustrated by the case of Kwazulu-Natal and Limpopo provinces - (:unkn) unknown (My University, 2010)
The object of this study is the dynamics of intergovernmental relations in South Africa and interactions between players taking part directly or indirectly in the definition and organization of the food security policy. Through the analysis of public policies approach, we exemplify these dynamics on the basis of a comparative study of food security policies in Limpopo and KwaZulu-Natal provinces in South Africa. We give an account of the comings and goings between different levels of the South African government, as well as those between the different players and international or national authorities, in the conception and organization of the policies. Thanks to the “prismatic effect” metaphor, our analysis identifies the divergences arousing from these comings and goings between the players, and highlights that their perceptions of the alimentary stakes are influenced and shaped by a series of social, economical and political circumstances which will “send” one or several interpretations of the problem. This leads to a dispersion effect of the original idea of “food security”, according to each player's representations and references concerning the subject, thus complexifying the definition and the organization of public policies. This study, far from setting out categorical conclusions, brings out new questions. It reveals in particular three difficulties that the public policy approach and the multi-level governance pose on a theoretical level and on the praxis level: (1) the opposition of empirical propositions; (2) the opposition between local government authorities and national government authorities in identifying public problems; and (3) the questions about the role of the multi-level governance approach in defining and organizing public policies. This invites us to explore new ways of approaching social facts and drawing the outlines of a social and political order which is yet uncertain.
Keywords: African Research